Identification of Wheat LACCASEs in Response to Fusarium graminearum as Potential Deoxynivalenol Trappers - Sun, Zhengxi; Zhou, Yilei; Hu, Yi; Jiang, Ning; Hu, Sijia; Li, Lei; Li, Tao (Frontiers in Plant Science, 2022)
Fusarium graminearum (F. graminearum) can cause huge yield reductions and contamination of grain with deoxynivalenol (DON), thus is one of the most problematic pathogen of wheat worldwide. Although great efforts have been paid and great achievements has been made to control the pathogens, there is still a wide gap for understanding the mechanism underlying F. graminearum resistance. Plant LACCASEs (LACs) catalyze the oxidative polymerization of monolignols, by reinforcing cell wall of various cell types, to provide mechanical support, xylem sap transportation and defence against pest and pathogens. To date, little has been known about LAC genes in bread wheat and their potential roles in wheat-F. graminearum interaction. Through systematic analysis of the genome wide homologues and transcriptomes of wheat, a total of 95 Triticum aestivum laccases (TaLACs) were identified, and 14 of them were responsive to F. graminearum challenge. 3D structure modelings of the 14 TaLAC proteins showed that only TaLAC78 contains the entire activity center for oxidation, and the others are lack of the type 1 copper ion ligand (T1Cu). Both amino acid sequence alignment and three-dimensional reconstruction after amino acid mutation showed that the loss of T1Cu is not only related to variation of the key amino acid coordinating T1Cu, but also closely related to the flanking amino acids. Significantly differential temporal expression patterns of TaLACs suggested subfunctionalization of them might occur. Promoter array analysis indicated that the induction of TaLACs may be closely associated with salicylic acid signaling, dehydration, and low-oxygen stress under F. graminearum infection. Molecular docking simulation demonstrated that TaLACs can not only catalyze lignin as a substrate, but also interact with deoxynivalenol (DON), which may be docked into the binding position of the monolignols, where the LACs recognizes substrates. The current study provides clues for exploring the novel functions of TaLACs in wheat resistance to F. graminearum, and TaLACs maybe candidates for conferring a high level of resistance against F. graminearum in wheat.